A Benchmark Dose Analysis for Maternal Pregnancy Urine‐Fluoride and IQ in Children. Issue 3 (8th June 2021) - Grandjean, Philippe; Hu, Howard; Till, Christine; Green, Rivka; Bashash, Morteza; Flora, David; Tellez‐Rojo, Martha Maria; Song, Peter X.K.; Lanphear, Bruce; Budtz‐Jørgensen, Esben
Abstract: As a guide to establishing a safe exposure level for fluoride exposure in pregnancy, we applied benchmark dose modeling to data from two prospective birth cohort studies. We included mother–child pairs from the Early Life Exposures in Mexico to Environmental Toxicants (ELEMENT) cohort in Mexico and the Maternal‐Infant Research on Environmental Chemicals (MIREC) cohort in Canada. Maternal urinary fluoride concentrations (U‐F, in mg/L, creatinine‐adjusted) were measured in urine samples obtained during pregnancy. Children were assessed for intelligence quotient (IQ) at age 4 ( n = 211) and between six and 12 years ( n = 287) in the ELEMENT cohort, and three to four years ( n = 407) in the MIREC cohort. We calculated covariate‐adjusted regression coefficients and their standard errors to assess the association of maternal U‐F concentrations with children's IQ measures. Assuming a benchmark response of 1 IQ point, we derived benchmark concentrations (BMCs) and benchmark concentration levels (BMCLs). No deviation from linearity was detected in the dose–response relationships, but boys showed lower BMC values than girls. Using a linear slope for the joint cohort data, the BMC for maternal U‐F associated with a 1‐point decrease in IQ scores was 0.31 mg/L (BMCL, 0.19 mg/L) for the youngest boys and girls in the two cohorts, and 0.33 mg/L (BMCL, 0.20 mg/L) for the MIREC cohort and the older ELEMENT children. Thus, the joint data show a BMCL in terms of the adjusted U‐F concentrations in the pregnant women of approximately 0.2 mg/L. These results can be used to guide decisions on preventing excess fluoride exposure in pregnant women.